Investigating high-density lipoprotein (HDL) subfractions, composition and functionality in people living with HIV - Hudson, Peter (Department of Medicine, 2023)
Background: Although antiretroviral therapy (ART) increases survival in individuals living with human immunodeficiency virus (HIV), this population faces an increased risk for cardiovascular disease (CVD). There is mounting evidence that the distribution, composition, and functionality of high-density lipoprotein (HDL) subfractions are altered in the presence of cardiovascular risk factors. We aimed to explore whether HIV and/or ART modulate HDL subfractions and functionality in a population of people living with HIV (PLWH). Methods: Fifty healthy HIV-negative control patients (HIV free control), 44 HIV-infected patients yet to receive any ART treatment (HIV ART-naïve) and 50 HIV-infected patients receiving ART (ART-treated) were included (South African cohort). HDL functionality was assessed by measuring reverse cholesterol efflux capacity, anti-oxidative activity (paraoxonase-1 (PON-1) activity) and anti-thrombotic activity (platelet-activating factor acetylhydrolase (PAF-AH) activity). HDL subfractions were measured using the Lipoprint® system. Results: HIV ART-naïve patients had lower HDL cholesterol than HIV-negative or ARTtreated patients (1.05 ± 0.46 vs 1.33 ± 0.39 vs 1.31 ± 0.74 mmol/L, respectively, p < 0.05). The percentage of the largest subfraction of HDL (HDL-1) was higher in HIV ART-naïve patients compared to HIV-negative patients (12.46 ± 6.33 vs 9.43 ± 4.41%, p< 0.05). The HIV ARTnaïve patients also displayed a change in HDL composition, with decreased levels of apolipoprotein A-I compared to HIV ART-treated patients and HIV-negative patients (38.5 ± 7.5 vs 43.8 ± 13.4 vs 45.5 ± 8.1 μmol/L, respectively, p < 0.05). Large HDL was inversely correlated with CD4+ count (r = -0.279, p < 0.01) and small HDL was positively correlated with CD4+ count (r = 0.333, p < 0.01). Although HDL functionality was not different between groups, PON-1 activity positively correlated with small HDL (r=0.19, p< 0.05). Conclusion: Our study suggests that HIV infection is associated with a change in HDL composition and a shift in HDL subfraction distribution, favouring a higher percentage of large HDL subfractions, which may contribute to the increased risk of CVD in HIV patients. More in-depth studies should be conducted to better understand the exact role of HIV and/or ART on the modification of HDL.